2020
DOI: 10.1186/s12891-020-03839-5
|View full text |Cite
|
Sign up to set email alerts
|

A multisite longitudinal evaluation of patient characteristics associated with a poor response to non-surgical multidisciplinary management of low back pain in an advanced practice physiotherapist-led tertiary service

Abstract: Background Non-surgical multidisciplinary management is often the first pathway of care for patients with chronic low back pain (LBP). This study explores if patient characteristics recorded at the initial service examination have an association with a poor response to this pathway of care in an advanced practice physiotherapist-led tertiary service. Methods Two hundred and forty nine patients undergoing non-surgical multidisciplinary management fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 63 publications
(91 reference statements)
0
11
0
Order By: Relevance
“…One study specifically evaluated the number of children living at home specifically (Dhondt et al., 2020). Number of children had no effect in all studies (Abu et al., 2017; Dhondt et al., 2020; Jensen et al., 2013; O’Leary et al., 2020; Stapelfeldt et al., 2011).…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…One study specifically evaluated the number of children living at home specifically (Dhondt et al., 2020). Number of children had no effect in all studies (Abu et al., 2017; Dhondt et al., 2020; Jensen et al., 2013; O’Leary et al., 2020; Stapelfeldt et al., 2011).…”
Section: Resultsmentioning
confidence: 91%
“…Outcome measures for pain and function were collected most frequently (Table 3). Marital status/partner had no effect on outcomes in eight studies (Beneciuk et al., 2013; Cougot et al., 2015; Jensen et al., 2013; Nava‐Bringas et al., 2016; Neyaz et al., 2019; O’Leary et al., 2020; Preuper et al., 2011; Stapelfeldt et al., 2011). One study demonstrated that having a partner or spouse was associated with better outcomes (Bath & Lovo Grona, 2015) and one study controlled for marital status/partner in the analysis (Sisco‐Taylor et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2019, LBP remained the major cause of years lived with disability (YLDs) worldwide despite a slight decline in the age-standardized prevalence, incidence, and YLDs rate from 1990 to 2019. In 2019, the highest prevalence rates were observed in the 80–84-year-old age bracket for both sexes globally, with the number of cases increasing with age and peaking between the ages of 45 and 54 years [ 2 ].…”
Section: Introductionmentioning
confidence: 99%